PERAN TEKNOLOGI DALAM MENINGKATKAN EFISIENSI SYSTEM AKUNTANSI KEUANGAN PEMERINTAH DAERAH KABUPATEN GORONTALO - Husain, Fauziah; Buliide, Adhar; Djauhari, Fingkan; Aminarti, Dini; Latada, Sri Melda (Media Mahardhika, 2025)
This study explores the role of technology in improving the efficiency of the financial accounting system of the Gorontalo District Local Government. Using a descriptive approach and qualitative analysis, the study collected data through a literature review, interviews with local government officials, observations, and document analysis. The results demonstrate that technologies such as e-accounting, cloud computing, and big data positively impact regional financial management by increasing transparency, accuracy, and the efficiency of financial reporting. Implementing a cloud-based accounting system in Gorontalo Regency accelerated the preparation of financial reports and reduced recording errors. Additionally, information technology encourages public participation in overseeing budget use. These findings underscore the importance of continued investment in technology and human resource training to promote more effective local financial governance.